Relevansi Filsafat Ilmu dalam Mengonstruksi Asas Keilmuan Pendidikan sebagai Dasar Peningkatan Mutu Pembelajaran di Sekolah - Ma'shumah Syamsir; Welly Ervina Solissa; Muhammad Syukur; M Ridwan Said Ahmad (Global Action and Education for Society, 2026)
Low learning quality in schools, as reflected in national literacy performance, limited higher-order thinking activities, and the dominance of teacher-centered instruction, indicates a fundamental issue within the epistemic structure of education. This study aims to examine the relevance of philosophy of science in constructing the foundational principles of educational science as a basis for improving learning quality in schools. The research employs a qualitative approach with a structured literature study design. Data were obtained through the selection of relevant scholarly sources, including educational policy documents, national performance reports, philosophy of science textbooks, and indexed research articles. Data analysis was conducted using content analysis techniques, involving data reduction, conceptual categorization, synthesis of findings, and the identification of relational patterns between empirical phenomena and the philosophical framework of science. The findings reveal that weak learning quality stems from the lack of integration among three core dimensions of educational science: ontology, epistemology, and axiology. Learners are not yet understood as active learning subjects; knowledge continues to be treated as a final object to be transmitted; and humanistic values have not become the foundation of instructional orientation. This conceptual fragmentation results in educational practices that are mechanistic and misaligned with scientific principles and the demands of the twenty-first century. The integration of philosophy of science provides a robust conceptual framework for reconstructing the foundational principles of educational science, enabling educators to develop learning processes that are more reflective, dialogical, critical, and value-oriented. The study affirms that improving learning quality requires the transformation of educators’ epistemic paradigms rather than mere technical innovation.